A review of chemistry and biological activities of the Indonesian Octocorallia - Masteria Yunovilsa Putra, Joko Tri Wibowo, Tutik Murniasih (Journal of Applied Pharmaceutical Science, 2017)
Marine invertebrates are known to produce secondary metabolites that may have potential as new drug candidates. Numerous chemical studies have shown that sponges are a rich source of marine bioactive compounds. However, recent studies demonstrate that octocorals also produce secondary metabolites with promising pharmacological activities. In this paper, we report on the chemical and biological activities of the Indonesian octocorals, particularly soft corals, gorgonians and sea pens. Octocorals from the Indonesian coasts have been demonstrated to contain a wide variety of compounds including steroids, sesquiterpenes and diterpenes. Cembranoid diterpenes have been largely founds in gorgonian and soft corals and they are believed to function as chemical defenses. Anti-inflammatory, antimicrobial, cytotoxic to antitumor have been disclosed for members of the cembranoid class.
Keywords: Marine invertebrates, octocorals, secondary metabolites, biological activities.